Juristic disputes over implementation of Qisas against a muslim who kills a non-Muslim - Amanullah, Muhammad (2013)
Perhaps the most sensitive issue relating to the Islamic penal system as it bears upon non-Muslims is the issue of whether or not a Muslim who kills a non-Muslim is liable to qisas, or just retribution, which in this case takes the form of the death penalty. Hanafi jurists maintain that a Muslim who intentionally kills a dhimmi (a non-Muslim who, for the payment of a poll-tax, enjoys security of his person and property in a Muslim country) or a mu`ahid (a non-Muslim who dwells within the dar al-Islam under a contract of protection) is indeed liable to qisas. Other Muslim jurists, such as Shafi`i, Malik and Ahmad hold that he is not liable. Modern scholars, such as `Awdah, El-Awa and others, have discussed the issue briefly. Based on classical and modern fiqh literature, I shall examine the principal arguments used by Hanafi jurists to support their position, and also explore arguments cited by the opposing camp. Finally I shall try to give preference to the opinion which is based on stronger proofs and which conforms to the present public interest of Muslims and non-Muslims all over the world.